Consider m and n positive integers; then,
![\begin{gathered} 2m-1 \\ 2n-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/oe9goosf3m3jy0vt5jw3hxhryb01ff8wy2.png)
are odd numbers; thus, the product of these two is
![\begin{gathered} (2m-1)(2n-1)=4nm-2m-2n+1 \\ \Rightarrow(2m-1)(2n-1)=4mn-2(m+n)+1 \\ \Rightarrow(2m-1)(2n-1)=2(2mn-(m+n))+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iv6hn5mznnpchh2kqpmjcylzxhhavxtsbs.png)
The first term is an even number (because it is multiplied by 2). If we add +1 to an even number, the result is an odd number; therefore, the product of two odd numbers is an odd number.
Consider the following odd and even numbers,
![\begin{gathered} 2j\to\text{ even} \\ 2k-1\to\text{ odd} \\ \Rightarrow2j+(2k-1)=2(j+k)-1=2p-1\to\text{ odd number} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/umyp6gma5htfrccecmaequtc065ks54og6.png)
Therefore, the odd+even=odd.
The mistake in the question is that 2x3 is a product of an even number by an odd number, not a product of odd numbers.
A counterexample is
![2+(3*5)=2+15=17\to\text{ odd}](https://img.qammunity.org/2023/formulas/mathematics/college/cfkta18ts8nft6zne0wlfgbd12i6vkglt1.png)